COPPER ACCUMULATION IN VINEYARD SOILS FROM NEMEA, GREECE - Kelepertzis, E.; Massas, I.; Fligos, G.; Panagiotou, M.; Argyraki, A. (Bulletin of the Geological Society of Greece, 2016)
We present for the first time the extent and magnitude of Cu accumulation in calcareous vineyard soils from Nemea, Greece, as result of intensive application of Cu-based fungicidal sprays. Surface (0-20 cm) soil samples were collected from 40 vineyard plots covering the whole agricultural region of Nemea devoted to viticulture. In 20 randomly selected vineyards, we also collected soil at 50 cm depth. Major soil properties were determined (pH, electrical conductivity, organic carbon and equivalent calcium carbonate contents, particle size distribution). Copper concentrations in Nemea vineyard soils (33.1 - 291 mg kg 1 ) were similar to those reported in the soils of vineyards in other parts of Europe. Copper has migrated down the soil profile since the levels at 50 cm depth are higher than the known background concentrations, probably as result of soil disturbance by tillage practices. We did not find differences in Cu availability between the surface and deep soil samples after applying the DTPA chemical extraction. The DTPA-extracted Cu concentrations were largely dependent on the total soil Cu content. The excessive application of Cu-based fungicides should be avoided with the aim to ensure that Cu accumulation does not reach levels that may inhibit plant growth.